Level of Utilization of Primary Health Care Services in a Selected Community in South-South Nigeria - Isabu, Augustina Chikaodili; Adhere, Ruth Enajirhevwe (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The study was on the Level of Utilization of Primary Health Care Services (PHCS) in Aguda-Epie community in Yenegoa Local Government Area of Bayelsa State. The aim was to determine the Level of Utilization of Primary Health Care Services in that community. It was a community based cross-sectional descriptive survey. Population consisted of 15,000 members of that community. A sample size of 330 respondents were selected by means of multi-stage sampling technique. Five objectives and four hypotheses guided the study. Instrument for Data collection was structured questionnaire schedule, (LUPHCSQ), which was validated both for face and content by experts. Reliability of the instrument was established by split –half method, with reliability co-efficient of r=.98. Collected datum were analyzed with SPSS 25 and interpreted using frequencies, percentages, Mean Scores and one-way ANOVA statistics. Result showed that, 1) all Primary Health Care Services (PHCS) were provided at the Comprehensive Primary Health Care Centre Agudama-Epie, 2) There is high level of awareness of PHCS among the respondents (an average score of 88.65%), 3) overall level of utilization of PHCS was low (Grand mean = 2.0 against the criterion mean of 2.5). 4) the most influencing factor of level of utilization of Primary Health Care Services in Agudama-Epie community are: non availability of 24 hours’ service, 303(91.8%), non-availability of advanced medical equipment 303(91.8%), non-availability of prescribed drugs, 280(84.8%). The study concluded that the level of utilization of PHCS is low and recommended that the media should be involved to educate citizens of availability and the need to make use of available PHCS to achieve the goal of universal health coverage.